1974
DOI: 10.1007/bf01221988
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic abnormalities observed in retina, pancreas and kidney of diabetic Chinese hamsters

Abstract: Summary. Intraeellular glycogen deposits were consistently found in the retina, kidney and pancreatic islets of diabetie-ketonurie Chinese hamsters. Accumulation of glycogen in the outer nuclear layer of the retina was mostly associated with severity of the disease, but was not related to age or sex. The type of retinal cell involved in the accumulation of glycogen was not clearly established. Itowever, the position of the affected cell, side by side with retinal neurons, suggests that the glycogen deposits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 14 publications
(16 reference statements)
0
16
0
Order By: Relevance
“…Therefore, glucose, glucose + arginine, and K + fail to cause normal release while theophylline and IBMX act more normally. Since excess amounts of glycogen are found in the diabetic B-cell, 58 Frankel has suggested that the relatively normal insulin responses to theophylline and IBMX might be due to synergism between cAMP and glucose derived from the large amount of intracellular glycogen. 5 The role of somatostatin in the pancreas of the diabetic Chinese hamster is not clear.…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…Therefore, glucose, glucose + arginine, and K + fail to cause normal release while theophylline and IBMX act more normally. Since excess amounts of glycogen are found in the diabetic B-cell, 58 Frankel has suggested that the relatively normal insulin responses to theophylline and IBMX might be due to synergism between cAMP and glucose derived from the large amount of intracellular glycogen. 5 The role of somatostatin in the pancreas of the diabetic Chinese hamster is not clear.…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…Diabetes mellitus is associated with progressive metabolic derangement, worsening glycemic control and morphological changes in the kidney, retina, pancreas and other organs [13]. Oxidative stress is known to play a significant role in the induction of these processes [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is associated with progressive metabolic derangement, worsening glycemic control and morphological changes in the kidney, retina, pancreas and other organs (Soret et al, 1974;Cristina et al, 2008;Cook et al, 2005). Oxidative stress is known to play a significant role in the induction of these processes (Giugliano et al, 1996;Baynes and Thorpe, 1999).…”
Section: Introductionmentioning
confidence: 99%